Sex-linked reproductive allocation in the dioecious shrub Pimelea microcephala subsp. microcephala (Thymelaeaceae) from four populations across a rainfall gradient. Issue 1 (2nd January 2023) - Draper, J. T.; Conran, J. G.; Simpson, B. S.; Weinstein, P.
ABSTRACT: Dioecy, the separation of sexes into different male and female plants, can enable sexes to independently develop optimal strategies for the sex-linked allocation of reproductive resources. Understanding how dioecious species vary as conditions become more or less favourable may affect conservation and revegetation efforts in arid environments. Our study investigated sex-related resource allocation in the Australian native shrub, Pimelea microcephala subsp. microcephala (Thymelaeaceae) at four sites across an annual rainfall gradient of 250–390 mm in semi-arid South Australia. The study measured 25 male and 25 female individuals for plant height, plant diameter, the number of inflorescences per plant, number of flowers per inflorescence and the ratio of reproductive to vegetative biomass. Significant differences in the ratio of biomass allocated to reproduction between sexes ( p  < 0.05) were detected at three of the four sites, with sex-related differences increasing with decreased annual rainfall. Female reproductive allocation was two to five times greater, and was less variable than males at all sites except the highest rainfall site ( p  < 0.05), while male reproductive allocation decreased with average annual rainfall ( p  < 0.05). Growth outcomes of males and females were equal and female reproductive traits were mostly consistent between sites and were not associated with rainfall, therefore population structure may remain stable for P. microcephala subsp. microcephala as habitats become drier, so long as pollen limitation does not occur.